2017
DOI: 10.1186/s12885-017-3881-5
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of colorectal cancer screening and recommendation behaviors among physicians in Korea

Abstract: BackgroundPhysician recommendations for colorectal cancer (CRC) screening have consistently been shown to be a strong predictor of screening. The aim of this study was to investigate perceptions of CRC screening modalities and recommendation behaviors among physicians in Korea.MethodsA cross-sectional, nationally representative survey conducted between November 2013 and February 2014. In total, 379 physicians (241 primary care physicians and 138 physicians affiliated with the Korean Association for the Study o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Our study is the first population‐based study to evaluate the knowledge and perceptions of CRC and CRC screening in a Chinese population. Although some similar studies were identified(Le et al, 2014; Ng et al, 2007; Shin et al, 2017; Wong et al, 2013, 2017), there was limited time trend comparison. Secondly, this study got a relatively large sample size compared with the previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Our study is the first population‐based study to evaluate the knowledge and perceptions of CRC and CRC screening in a Chinese population. Although some similar studies were identified(Le et al, 2014; Ng et al, 2007; Shin et al, 2017; Wong et al, 2013, 2017), there was limited time trend comparison. Secondly, this study got a relatively large sample size compared with the previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Further research will explore FDs clinical practice to identify activities and attitudes associated with successful or unsuccessful adherence rates. Diffidence toward cancer screening and/or the preference of screening modalities other than fecal testing could possibly explain the different FDs attitude [3234].…”
Section: Discussionmentioning
confidence: 99%
“…This means that their decision to take part in the NCSP is voluntary and without any advice. Therefore, considering the major role of general practitioners or family doctors in increasing participation rates [ 20 , 21 , 22 ], improving the perception of cancer screening in the medical staff of a community has been suggested to increase participation.…”
Section: Discussionmentioning
confidence: 99%